Total synthesis of (-)-isatisine A - Patel, Pitambar; Ramana, C. V. (Journal of Organic Chemistry, 2012)
A modular total synthesis of (-)-isatisine A is described in which four consecutive metal-mediated transformations have been employed at the final stage. These include [Pd]-catalyzed Sonogashira coupling, [Pd]-catalyzed nitroalkyne cycloisomerization leading to isatogens, and addition of indoles to isatogens using InCl3- and [Rh]-catalyzed oxidative N-heterocyclization of amino alcohol to form the key amide bond. In addition to these, the removal of the protecting groups has also been carried out in a selective fashion employing either catalytic or stoichiometric metal/metal-based reagents.